The Impact of Active Learning and the Recitation Method on Student Learning Outcomes in Islamic Education: A Case Study at Integrated Islamic Junior High School? - Sainab, Sainab; Nasution, Baktiar; Rahman, Abdul (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
This study investigated the impact of active learning and the recitation method on student learning outcomes in Islamic education at Integrated Islamic Junior High School Humairoh Siak Hulu. The research aimed to determine whether these instructional strategies significantly improved student achievement compared to conventional teaching approaches. A quantitative experimental design was employed with 74 students from two classes. The students were assigned to experimental groups using active learning and the recitation method, and their performance was measured through pre-test and post-test assessments. Data analysis using an independent samples t-test and analysis of variance (ANOVA) revealed significant differences in learning outcomes between students taught with active learning and the recitation method and those taught with traditional approaches (p < .05). The findings indicate that both active learning and the recitation method positively influence students' comprehension and retention in Islamic education. These results suggest that interactive and participatory learning methods can enhance academic performance and foster deeper engagement with religious content. The study highlights the importance of innovative pedagogical strategies in Islamic schools to strengthen student-centered learning and improve educational quality.